Management of water resource based on local wisdom: a develompment study of Kampung Naga as field laboratory of Geography Education in Tasikmalaya, West Java. (March 2019) - As'ari, R; Rohmat, D; Darsiharjo; Maryani, E; Ningrum, E
Abstract: Kampung Naga is a traditional village in Tasikmalaya, West Java which is unique in environmental management with a sustainable principle. The geography phenomenon in Kampung Naga can be developed through environmental conditioning as a geography education field laboratory. Field observations and field visits are the most basic needs of geography. The development of field laboratories can be developed by selecting locations that have the complexity of geographic phenomena. The purpose of this study was to study the management of water resources based on local wisdom as a study of the development of Kampung Naga as a Geography Education Field Laboratory. The method used in this study is qualitative descriptive. The steps of the research carried out are as follows: 1) delineation of Naga village area using satellite image data and maps, 2) data collection and inventory through surveys and interviews, 3) data processing by analyzing data to model water resource management based on the local wisdom of the indigenous people of Kampung Naga. The results showed that water management in Naga village had a pattern: water was used for rice irrigation, drinking, washing and bathing, and vegetation and animal habitat, the water source in Kampung Naga came from the Ciwulan river, and there was a pattern of water utilization by following the spatial pattern Kampung Naga village area with the concept of water conservation with forest conservation. Kampung Naga can be used as a field laboratory for Geography education, one of them is about the material of Hydrosphere in the material of water resources management.